See no isotropy, hear no isotropy: Perceived distance anisotropy in auditory space - Šoškić Anđela; Stublinčević Marija; Tošković Oliver (Psihologija, 2024)
The aim of the present study was to investigate whether the tendency to perceive vertical distances as larger than horizontal ones, called the anisotropy of perceived distance, exists in the auditory modality, too. We performed two experiments in which participants (16+20) had a task to match distances of two sound sources, positioned on horizontal and vertical axes, on three egocentric distances. Besides that, in the second experiment, we varied the head moving towards a sound source (with and without) and sound dispersion around the head (with or without a box-like frame around the head). Results showed that participants managed to differentiate sound source distances, but the effects of head moving (proprioceptive information) and sound dispersion around the head were not obtained. Finally, results showed differences in matched distances between two directions. Distances of the vertical sound source were systematically perceived as larger than physically equal horizontal ones, which coincide with findings from previous studies, related to visual or proprioceptive distance estimates.